The Influence of Price Perception and Product Quality Perception on Purchase Intention toward Local Bag Brand - Rashaky Arya Vito (Journal of Management and Business Innovations, 2026)
This research investigates how consumers’ views on price and product quality impact their intention to purchase Lataphat Leather Goods using the Theory of Planned Behavior (TBP). The use of high-quality materials leads to higher product prices, prompting an inquiry into whether consumers’ perceptions of price and quality affect their purchasing intentions. This study utilized a quantitative causal methodology with 100 respondents selected through purposive sampling. Data collection involved a Likert-scale of five-point questionnaire, which was analyzed utilizing PLS-SEM via SmartPLS ver. 4. The results illustrate that both price perception and product quality perception significantly and positively influence purchase intention, with price perception having a slightly greater impact. These findings affirm that consumers' cognitive assessments of price and product quality are crucial factors influencing their purchase intentions. This study enhances the application of TPB regarding local bag products and offers practical recommendations for effective pricing and product development strategies. However, the findings are limited to a single local bag brand and two explanatory variables, which may restrict their generalizability to other products and contexts. Keywords: Local Brand, Price Perception, Product Quality Perception, Purchase Intention, Theory of Planned Behavior